Salivary pH changes post nasopharyngeal carcinoma radiotherapy using linac x- ray - Azhari Azhari; Yohanes Hutasoit; Ary C. Permana; Setiawan Soetopo (Journal of Dentomaxillofacial Science, 2018)
Objective: The purpose of this study was to obtain an illustration of saliva pH in patients undergoing radiotherapy with linac x-ray radiation for nasopharyngeal carcinoma. Radiation therapy for nasopharyngeal carcinoma frequently caused severe salivary gland dysfunction. The salivary gland dysfunction possibly influenced saliva pH.Material and Methods: The study was a simple descriptive. This study was conducted on 7 males and 2 females undergoing radiation therapy with linac x-ray for nasopharyngeal carcinoma. The measurement of saliva pH was done using an electrode pH meter.Results: This study shows that the range of saliva pH in 9 patients undergoing radiation therapy is 5.34 to 6.19.Conclusion: That saliva pH in 9 patients undergoing radiation therapy with linac x-ray radiation for nasopharyngeal carcinoma at Dr. Hasan Sadikin Hospital is lower than its normal value.